Charge trapping and coalescence dynamics in few layer MoS2. (16th October 2017) - Vega-Mayoral, Victor; Borzda, Tetiana; Vella, Daniele; Prijatelj, Matej; Pogna, Eva A A; Backes, Claudia; Coleman, Jonathan N; Cerullo, Giulio; Mihailovic, Dragan; Gadermaier, Christoph
Abstract: The optoelectronic properties of a material are determined by the processes following light-matter interaction. Here we use femtosecond optical spectroscopy to systematically study photoexcited carrier relaxation in few-layer MoS2 flakes as a function of excitation density and sample thickness. We find bimolecular coalescence of charges into indirect excitons as the dominant relaxation process in two- to three-layer flakes while thicker flakes show a much higher density of defects, which efficiently trap charges before they can coalesce.